Pakiramdaman isang tatak Filipinong lapit sa pagdadalumat sa Sosyolohiya (pakiramdaman: a filipino brand of reflective inquiry in Sociology) - Erasga, Dennis S. (Humanities Diliman, 2015)
The article contends that neither theory-building nor theorizing is an exclusive means of understanding the social in Philippine sociological discourse. Pagdadalumat as a homegrown reflexive inquiry proves to be more proficient and powerful an approach in making sense of the foundational principles of the discipline. Henceforth, the article examines the two implicated issues of doing pagdadalumat in the production of sociological knowledge in the Philippines viz. (i) the concept of kapwa as manifestation of the nexus of the Self and Other (ii) and the epistemological affordances of pagdadalumat versus the rigid evidence-seeking temperament of scientif ic inquiry. At the end, an outline of a sociological model of pagdadalumat is presented—pakiramdaman—anchored on an indigenous communicative practice (pakikipagtalastasan) using four (4) Filipino social constructs—lapit, galang, hiya, lusot—and their corresponding indicators—relasyon, kapwa, sitwasyon, kahihinatnan.